Strategy for digital transformation of chemical engineering in Ukraine during war - Piddubnyi, Mykyta V.; Krivileva, Svetlana P. (Національний технічний університет "Харківський політехнічний інститут", 2025)
This article delves into the concept of Industry 4.0 as a transformative force in modern manufacturing, with particular focus on its impact on Ukraine’s chem-ical engineering and mechanical industries. It explores the core technologies driving Industry 4.0 – including cyber-physical systems, the Internet of Things (IoT), artificial intelligence (AI), big data, and cloud computing – and emphasizes how their implementation can drive productivity, efficiency, and innova-tion in manufacturing processes. Special attention is given to enterprises within Ukraine's chemical engineering sector, highlighting the specific challenges they face amid the ongoing 2014–2025 war with Russia, which has severely damaged industrial capacities in the northern, eastern, and southern regions of the country. The study identifies how the adoption of Industry 4.0 technologies is not just an opportunity but a necessity for Ukraine’s industrial recovery and internation-al competitiveness. Through a comprehensive SWOT analysis, the article evaluates internal strengths (such as skilled human capital and integration with the global IT sector), weaknesses (including limited financial resources and outdated infrastructure), opportunities (such as access to EU programs and export potential in dual-use technologies), and threats (from war-induced destruction, investor insecurity, and brain drain). Special focus is placed on how enterpris-es in chemical engineering machinery can benefit from technological foresight, digital transformation, and circular economy principles to rebuild and mod-ernize in a sustainable way. У статті розглядається концепція Індустрії 4.0 як потужний фактор трансформації сучасного виробництва, з особливим акцентом на її вплив на підприємства хімічного машинобудування та механічної галузі в Україні. Аналізуються ключові технології Індустрії 4.0 – кіберфізичні системи, Інтернет речей (IoT), штучний інтелект (AI), великі дані та хмарні обчислення – та підкреслюється, як їх впровадження сприяє підвищенню ефективності, гнучкості та інноваційності виробничих процесів. Особливу увагу приділено підприємствам хімічного машинобудування в умовах триваючої війни з Росією (2014–2025), яка призвела до руйнування цілих промислових кластерів у північних, східних та південних регіонах України. У дослідженні зазначено, що інтеграція технологій Індустрії 4.0 – це не просто шанс, а критично важлива умова для відновлення української промисловості та підвищення її конкурентоспроможності на міжнародному рівні. Проведено SWOT-аналіз, що охоплює внутрішні сильні сторони (наявність кваліфікованих кадрів, інтеграція з глобальним ІТ-сектором), слабкі сторони (нестача фінансів, застаріла інфраструктура), можливості (доступ до європейських програм, експортний потенціал у сфері двофункціональних технологій) та загрози (руйнування інфраструктури, інвестиційна непривабливість, еміграція інженерів).
Стратегія цифрової трансформації хімічної інженерії України під час війни
Keywords: chemical engineering; industry 4.0; digitization; technologies; modernization; SWOT analysis; хімічна інженерія; індустрія 4.0; цифровізація; проектування і управління процесами; модернізація; SWOT аналіз